Pengaruh Sistem Pengendalian Internal, Proteksi Awig-Awig, Keyakinan Hukum Karma Phala Terhadap Kecenderungan Kecurangan Akuntansi Pada LPD Se-Kecamatan Mengwi - Gusti Ayu Putu Helenia; Ni Komang Sumadi; Ni Putu Ayu Kusumawati (Hita Akuntansi dan Keuangan, 2025)
LPD, an unique economic entity in Balinese culture introduced by the Governor of Bali, Prof. Dr. Ida Bagus Mantra in 1984, has proven its role in achieving economic equality among Balinese communities from rural areas to major cities, becoming the only small-scale financial institution owned by indigenous communities in Bali and adhering to Bali's distinctive economic principle known as "bebanjaran". The research aimeds to determines the level of tendency towards accountings fraud in LPDs in the Mengwi District, Badung Regency. Tshe data in this studys were obtaineds from questionnaires or primary data. The subjects of the study weres 39 LPDs in the Mengwi District, Badung Regency, with a totaly of 113 LPD employees. The resultss indicate that effective internal controls systems and Awig-awig protection haves a negative impacts on thes tendenrcy towards accounting frauds, whiles belief in the karma phala law does not significantly influence the inclination towards accounting fraud. For LPDs in the Mengwi District, it is recommended to enhance internal control systems, implement Awig-awig protection, and increase employee awareness of the legal and moral consequences of fraudulent actions to ensure security, integrity, and accountability in managing village funds and assets effectively, thereby strengthening public trust in the institution.